2013
DOI: 10.4161/onci.23562
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-associated macrophages subvert T-cell function and correlate with reduced survival in clear cell renal cell carcinoma

Abstract: Although malignant cells can be recognized and controlled by the immune system, in patients with clinically apparent cancer immunosurveillance has failed. To better understand local immunoregulatory processes that impact on cancer progression, we correlated intratumoral immunological profiles with the survival of patients affected by primary clear cell renal cell carcinoma (ccRCC). A retrospective analysis of 54 primary ccRCC samples for 31 different immune response-related transcripts, revealed a negative cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
131
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(138 citation statements)
references
References 50 publications
5
131
1
1
Order By: Relevance
“…CTLs subsequently activated by such Treg-preconditioned DCs that had lost their costimulatory capacity showed enhanced coinduction of PD-1 and TIM-3, which may directly render them dysfunctional, or make them more susceptible to the induction of dysfunction through continued stimulation in a low CD80/86 context, where coinhibitory signals cannot be balanced by costimulatory signals (60). Interestingly, tumor-associated macrophages from human cancer patients also induce PD-1 and TIM-3 expression in autologous T cells (61), which suggests that this property is not limited to DCs.…”
Section: Discussionmentioning
confidence: 99%
“…CTLs subsequently activated by such Treg-preconditioned DCs that had lost their costimulatory capacity showed enhanced coinduction of PD-1 and TIM-3, which may directly render them dysfunctional, or make them more susceptible to the induction of dysfunction through continued stimulation in a low CD80/86 context, where coinhibitory signals cannot be balanced by costimulatory signals (60). Interestingly, tumor-associated macrophages from human cancer patients also induce PD-1 and TIM-3 expression in autologous T cells (61), which suggests that this property is not limited to DCs.…”
Section: Discussionmentioning
confidence: 99%
“…36 A recent study on tumor-associated macrophages in RCC describes an association of the number of CD68C macrophages with a shorter survival as well as an accumulation of M2 type macrophages expressing the scavenger receptor CD163 and the interferon regulatory factor 4 in ccRCC. 37 Other authors investigated the intratumoral balance of polarized tumor-associated macrophages and showed that especially CD206/mannose receptor-positive macrophages (M2 type) are associated with reduced survival in RCC patients. 38 Recently, markers for human MDSC have been developed (e.g., CD14CHLA-DRlow) therefore the inclusion of myeloid cells in flow cytometric analyses would be a worthwhile approach in future studies.…”
Section: E985082-6mentioning
confidence: 99%
“…4,5,21 Macrophage populations in tumors are known to be heterogeneous with varying proportions of M2 and M1 macrophages. Recent clinical studies suggest a correlation between the presence of M1-skewed CD68C HLA-DRC iNOSCmacrophages and clinical outcome in tumors such as non-small cell lung cancer, pancreatic cancer, colorectal cancer, ovarian cancer, and renal cell carcinoma [32][33][34][35][36] ). NO-producing macrophages can be cytocidal in vitro against tumor cells, 37,38 but formal evidence for in vivo cytoxicity against solid tumors is lacking.…”
Section: Discussionmentioning
confidence: 99%